Late Bronze Age flintworking from ritual zones in Southern Scandinavia - Masojć, Mirosław (Archaeopress, 2016)
This work is devoted to flintworking encountered in the so-called cult houses and ritual zones from the Late Bronze Age in southern Scandinavia, where thousands of barrows were built in the period from the Neolithic to the end of the Early Bronze Age.